PERSEPSI MAHASISWA TERHADAP PELAKSANAAN PEMBELAJARAN DARING PADA JURUSAN PGSD - Winara Winara; Demmu Karo-Karo (Universitas Negeri Medan, 2021)
Online learning requires evaluation both in terms of the delivery of the media teaching staff used and the maximum learning response from adult students. Learning that is not face to face certainly requires special attention to achieve effective learning goals. Disturbances during online are also a problem of internet network disruption, the online application learning media used by this educator who became a researcher to conduct questionnaire research on PGSD students consisting of 426 students consisting of 4 batches namely 2017,2018,2019 and 2020 to make respondents in research. Researchers conducted a questionnaire via google form, there were 8 questions related to online learning questions covering activities during online learning. Student responses to online learning carried out by lecturers are good overall 90% of student responses to online learning are very good, but 10% of student responses have not felt satisfaction or are lacking in online learning.Keywords: Student Perception, Online Learning